SOCIAL FUND AND THE HIERARCHY OF MUHAMMADIYAH ORPHANAGES FINANCIAL INDEPENDENCY - Utami, Yuli; Azhari, Azmi Najmimudin; Sawarjuwono, Tjiptohadi; Alhadi, Abu Azam (Jurnal Ekonomi & Studi Pembangunan, 2019)
This study aims to analyze the Muhammadiyah social fund and the hierarchy of financial independence of seven its orphanages in the Province of Daerah Istimewa Yogyakarta. This study utilizes primary data which is obtained from interview, questionnaire, document studies, and observations; and analyzed using Analytical Hierarchy Process and SWOT approaches. It finds that the orphanages have the same type of fund resources which collected from the donors, namely, permanent donor (the top priority), incidental, social service and government, permanent business, and seasonal business. Meanwhile, the orphanage funds were allocated to the foster children’s skill improvement, foster children’s tuition fee, orphanages development fund, orphanages activities, kitchen support/daily needs, orphanage’s saving/investment and foster children’s saving/investment. Four of out seven orphanage funds prior allocation went to the foster children’s skill improvement, while the rest, to the orphanage development, foster children’s saving/investment, and orphanage’s saving/investment. It indicates the dependency of the orphanages financial sources toward the donors, or lacks their own investment, despite some are better-off by starting their own-business. These finding could be benefited for the orphanages in managing the social funds for investment and mapping the potential as well as the development of the orphanage financial independence in their future strategies